2006
DOI: 10.1371/journal.pbio.0040225
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Ascidian Epidermal Sensory Neurons: Insights into the Origin of the Chordate Peripheral Nervous System

Abstract: The vertebrate peripheral nervous system (PNS) originates from neural crest and placodes. While its developmental origin is the object of intense studies, little is known concerning its evolutionary history. To address this question, we analyzed the formation of the larval tail PNS in the ascidian Ciona intestinalis. The tail PNS of Ciona is made of sensory neurons located within the epidermis midlines and extending processes in the overlying tunic median fin. We show that each midline corresponds to a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
235
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(252 citation statements)
references
References 80 publications
14
235
2
1
Order By: Relevance
“…In contrast, in the chordate lineage, the hedgehog-positive cells are only retained ventrally. The ventral PNS of amphioxus 33 and ascidians 34 may be evolutionary remnants, homologous to the dorsal nerve cord of hemichordates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the chordate lineage, the hedgehog-positive cells are only retained ventrally. The ventral PNS of amphioxus 33 and ascidians 34 may be evolutionary remnants, homologous to the dorsal nerve cord of hemichordates.…”
Section: Discussionmentioning
confidence: 99%
“…The cell bodies of ESNs lie in the rostral-dorsal epidermis of the trunk and midline epidermis of the tail with long processes extending to the cuticular fin (Ohtsuka et al, 2001b;Takamura, 1998). Previous studies on Ciona intestinalis have shown that caudal ESNs are derived from the b4.2 and that caudal ESN formation is controlled by FGF, Nodal, anti-dorsalizing morphogenetic protein (ADMP) and Delta/Notch (Hudson and Lemaire, 2001;Pasini et al, 2006). However, it was not determined when and where these signaling pathways play roles in ESN specification.…”
Section: Introductionmentioning
confidence: 99%
“…Negative (or very low) p-Smad1/5/8 staining was observed in buds and embryos. The weak p-Smad1/5/8 staining in embryos contradicted the well documented BMP input to the heart and nervous systems specifications, described in other ascidians (Pasini et al, 2006;Christiaen et al, 2010). Therefore, functions in the B. schlosseri BMP pathways should be further studied.…”
Section: Discussionmentioning
confidence: 76%
“…In solitary ascidian species, STP expression and functions during ontogenic stages have been elucidated for Wnt/b-catenin (Niwano et al, 2009;Hudson et al, 2013), TGF-b (Kobayashi et al, 1999;Kobayashi and Makabe, 2001;Hino et al, 2003;Kawashima et al, 2005;Christiaen et al, 2010;Nishide et al, 2012) and MAPK/ ERK (Bertrand et al, 2003;Hudson et al, 2003;Nishida, 2003;Pasini et al, 2006;Chambon et al, 2007;Sakabe et al, 2006) pathways alone, or in combination with other STPs (Hudson et al, 2007;Lemaire, 2009;Pasini et al, 2012;Sasakura et al, 2012;Squarzoni et al, 2011). This has not been extensively studied in colonial species where astogenic and ontogenic pathways are developing side by side and in concert.…”
Section: Discussionmentioning
confidence: 99%